TGGE-monitoring of the microbial community along the olive mill wastewaters anaerobic treatment - Eusebio, Ana (2010)
Monitoring the microbial community present during the olive mill wastewater (OMW) anaerobic treatment was carried out using PCR-TGGE analysis. Phase-contrast microscopy was used in order to directly examine microbial cells morphology. Samples were collected from the anaerobic digester bottom along the successive increases of OMW loading rate. TGGE banding patterns showed a significant diversity of OTUs. Cluster analysis of TGGE banding patterns shows two major groups: one cluster composed of samples belonging to the initial phases of treatment and a second cluster that encloses the other two samples. According to BLAST results, four sequences affiliated with group Cytophaga-Flexibacter-Bacteroidetes (CFB), one with sub-class Epsilon-Proteobacteria and other with phylum Firmicutes. The sequences obtained from each band were used to construct phylogenetic trees, and also using bacterial 16S rDNA sequences from environmental clones and reference taxa. Archaeal 16SrDNA PCR detection analysis revealed the presence of Archaea only in the initial sample of the digester start-up suggesting that methanogenesis along the treatment process occurs at an upper level of the unit. Concerning microscopic observations, the more representative morphological forms found in the bottom of digester were Clostridium spp. and Clostridium spp. sarcina-like forms.